Evaluación de un sistema de poligeneración para la sostenibilidad energética en el corregimiento Cañaveral-Bolívar (2020)
The Master’s project contemplates implementing a polygeneration system using reviewable energetic resources such as solar, Eolic and diesel fuel as a backup in generating electric energy to guarantee sustainability and reliability for providing the service to the community in the Olivos sector in the township of Cañaveral Municipality of Turbaco, Bolivar. The system is integrated by a photovoltaic solar station, a medium power eolic energy plant, and a diesel generator. By implementing the system, we seek to guarantee the minimum daily consumption of 35 homes in the area. The project was done in the following stages: 1. Describe the polygeneration, technical, economic and environmental balance concepts. 2. Characterize the energy demand in the influence zone and characterize the potential of energetic resources available in the study zone through a data base. 3. Analyze the technical economic feasibility of the polygeneration system by modeling with specialized software. The methodology used is mixed by integrating the sub-studies in all the phases of the project. The system simulation through the Homer Pro software gave an NPV of $1,045.869.000.00 COP, operation cost $34, 351.610.00 COP and a LCOE 963.38 $/kWh. The system generates 211.517 kWh/year, the eolic system 162.918 kWh/year, photovoltaic system 41.417 kWh/year, and the diesel 7,182 kWh/year, with a participation of 77%, 19.6% y 3.4% respectively.